Performance Evaluation of Real Estate Sector to Fulfill Urban Housing Demand: A Case Study of Monsurabad Housing Estate Pabna, Bangladesh - Mazed Parvez (International Journal of Information Systems and Informatics, 2020)
Bangladesh is one of the in large part populated countries in the sector. With the urbanization fashion, the populace within the city location is increasing every day. These days the population is about 30 million, and on the 12 months 2040, it has miles anticipated at about two hundred million. With the growing city population, housing calls for in will increase every day. However, the call for will increase the high-quality of urban housing decline. Pleasant residence with a better carrier facility cannot be ensured. Non-public housing gives first-rate city housing, which is needed. The real estate area contributes to quality housing to fulfill city housing demand. Pabna is one of the quickest growing cities in Bangladesh. The city has a populace of about 116305 with this huge populace like different towns of Bangladesh, Pabna cannot provide suitable housing to the city dwellers. Monsurabad housing estate, a real estate corporation placed at Pabna, affords housing facilities to urban dwellers. This observation aimed to determine the contribution of real property zone most of the urban housing and the overall performance of housing facility presents through the real estate region. From this overall performance assessment, a new manner will emerge with the aid of which the private sector contribution to fulfill the city housing demand might be determined and cannot apprehend the fine of housing furnished through the real estate area. This has a look at also consists of some lacking of actual estate quarter and recommends overcoming the missing. Subsequently, the examination could explain how the low- and middle-magnificence-income level humans may be afforded on the entire real estate.